Investigation of the effect of a virtual reality-based imagery training model on muscle activation in athletes - Bedir, Fatih; Bedir, Deniz; Yılmaz, Hasan Hüseyin; Ağduman, Fatih; Şen, İlhan; Kıyıcı, Fatih; Korkmaz, Onur Erdem; Yıldız, Mustafa Onur; Çelik, Erkan (Frontiers in Psychology, 2025)
IntroductionIn the field of sports psychology, imagery training plays a significant role in enhancing athletes’ mental preparation and optimizing sports performance. This study aims to investigate the effects of the Virtual Reality-Based Imagery (VRBI) training model on muscle activation and kinesthetic motor imagery skills in athletes. Specifically, the study compares the VRBI model with traditional imagery methods, including Visual Motor Behavior Practice (VMBP) and Video Modeling (VM), to determine its effectiveness in improving neuromuscular responses.MethodsA quasi-experimental design with repeated measures was employed, involving 30 bodybuilders and fitness athletes who were randomly assigned to VRBI, VMBP+VM, and control groups. Muscle activation was measured using surface electromyography (sEMG) across a 12-week intervention period. The intervention protocols included progressive relaxation, video modeling, and imagery exercises tailored to enhance kinesthetic motor imagery skills.ResultsThe results revealed that the VRBI model significantly increased muscle activation levels and kinesthetic motor imagery skills compared to both the VMBP+VM and control groups (p < 0.01). Notably, athletes in the VRBI group achieved peak muscle activation one week earlier than those in the VMBP+VM group, demonstrating a faster adaptation process. Additionally, VRBI training led to a more substantial improvement in imagery skills, suggesting its superiority in mental training interventions.Discussion and conclusionThe VRBI model offers a more effective approach to enhancing muscle activation and kinesthetic motor imagery skills in athletes. These findings highlight the potential of VRBI as a valuable tool for optimizing sports performance and accelerating peak performance achievement.